Screening and characterization of novel biosorbent for the removal of Cadmium from contaminated water - Md Motakabber Ali; Balaram Sarkar; Barsha Sarkar; Parijat Bhattacharya; Niloy Chatterjee; Sukanta Rana; Md Rokunuzzaman; Jatindra Nath Bhakta (Energy Nexus, 2024)
Presence of trace metal pollutants in the aquatic system is a worldwide foremost concern. The present investigation was an attempt to find out the novel biosorbent for the removal of Cadmium(CdII) from contaminated water. The leaf of Sesbania bispinosa was screened out as a potential Cd(II) removing biosorbent from thirty different natural biomasses by physico-chemical and sorption process characterizations. Biosorption capacity of S. bispinosa was determined by batch mode biosorption method with the functions of solution pH, contact time, biosorbent dose and initial Cd(II) concentration. Obtained results were analyzed for isotherm and kinetic study. The S. bispinosa biosorbent exhibited the biosorption equilibrium of Cd(II) uptake in 30 min. At pH 4, biosorbent dose of 1 g/L was sufficient for maximum Cd(II) uptake. Scanning Electron Microscopy (SEM) images and Fourier Transform Infrared Spectroscopy (FTIR) spectra confirmed the favourable sorption surface characteristics. The data also demonstrated that Freundlich isotherm (R2=0.998) is the better fitted model compared to Langmuir model and the maximum sorption capacity was found to be 33.33 mg/g. Suitabilty of pseudo second order reaction pathway was observed during the kinetic study. Most especially, The selected biosorbent is ascertained effective in removing multimetals [Cd(II) - 67.51 %, Cr(VI) – 40.36 %, Pb(II) – 100 % and Cu(II) – 59.01 %] from a quaternary aqueous solution of Cd(II), Cr(VI), Pb(II) and Cu(II) mixture and spent biosorbent can be easily regenerated by applying 0.1 M HCl solution as a desorbing agent. It, therefore, could be concluded that leaves of S.bispinosa might be a low-cost and environmentally sound novel biosorbent for the treatment of Cd(II) contaminated water.